Hypothermia attenuates apoptosis and protects contact between myelin basic protein‐expressing oligodendroglial‐lineage cells and neurons against hypoxia–Ischemia. Issue 10 (28th May 2014) - Ichinose, Mari; Kamei, Yoshimasa; Iriyama, Takayuki; Imada, Shinya; Seyama, Takahiro; Toshimitsu, Masatake; Asou, Hiroaki; Yamamoto, Masahiro; Fujii, Tomoyuki
<x xml:space="preserve">Abstract</x> Periventricular leukomalacia (PVL) is a major form of brain injury among preterm infants, which is characterized by extensive loss and dysfunction of premyelinating oligodendrocytes (pre‐OLs) induced by hypoxia–ischemia (HI). Therapeutic hypothermia, which is a standard treatment for term infants with HI encephalopathy, is not indicated for preterm infants because its safety and effect have not been established. Here we investigate the effectiveness and mechanism of hypothermia for the inhibition of pre‐OLs damage in PVL. For in vivo studies, 6‐day‐old rats underwent left carotid artery ligation, followed by exposure to 6% oxygen for 1 hr under hypothermic or normothermic conditions. The loss of myelin basic protein (MBP) was inhibited by hypothermia. For in vitro studies, primary pre‐OLs cultures were subjected to oxygen–glucose deprivation (OGD) under normothermic or hypothermic conditions, and dorsal root ganglion neurons were subsequently added. Hypothermia inhibited apoptosis of pre‐OLs, and, despite specific downregulation of 21.5‐ and 17‐kDa MBP mRNA expression during hypothermia, recovery of the expression after OGD was superior compared with normothermia. OGD caused disarrangement of MBP distribution, decreased the levels of phosphorylated 21.5‐kDa MBP, and disturbed the capacity to contact with neurons, all of which were restored by hypothermia. Pharmacological inhibition of ERK1/2 phosphorylation with U0126 during and after OGD significantly reduced the protective effects of hypothermia on apoptosis and myelination, respectively. These data suggest that phosphorylated exon 2‐containing (21.5‐ and possibly 17‐kDa) MBP isoforms may play critical roles in myelination and that hypothermia attenuates apoptosis and preserves the contact between OLs and neurons via ERK1/2 phosphorylation. © 2014 Wiley Periodicals, Inc.